Factors associated with clinical competence in the gynecologic oncology subspecialty rotation of obstetrician-gynecologist (OB-GYN) residents - Dy Echo, Ana Victoria V.
Although a Gynecologic Oncology rotation is assumed to help residents achieve clinical competence, variations in the factors of the rotation exist. This correlation study was conducted in a University Hospital to determine whether factors of the subspecialty rotation are associated with clinical competence. Thirty-one residents rotating in Gynecologic Oncology were recruited. They were given multiple choice question (MCQ) examination and underwent skills evaluation pre- and post rotation. They completed a logbook, listing all their learning activities during the rotation, as well as the number of cases seen. Difference in pretest and posttest scores was determined using paired t-test. Association of factors with clinical competence was determined using chi square and Pearson correlation coefficient. There was a statistically significant increase in the overall scores (p=0.001) and in the skills score (p=0.025), but not in the knowledge (p=0.042). Mean posttest knowledge score reached passing level, but mean posttest skills and overall scores did not reach passing level. Training institution (internal residents, p=0.000), academic aptitude (grade>60%, p=0.009), and duration of rotation (>2 weeks, p=0.001) were associated with clinical competence. Conference (r=0.661) and outpatient duty (r=0.679), case load (r=0.615), having fellows as teachers (r=0.665) and active participation (r=0.652) were strongly associated with clinical competence. Bedside teaching (r=0.591) and inpatient duty (r=0.599), and having consultants as teachers (r+0.487) were moderately associated with clinical competence. Passive participation (r=0.261) was weakly associated with clinical competence. In this study, residents did not achieve clinical competence in Gynecologic Oncology as a result of the rotation. Residents from a training institution with a Gynecologic Oncology fellowship training program and with academic aptitude > 60% are more likely to achieve clinical competence. Increasing rotation duration to > 2 weeks, time spent in the different activities, case load, fellows and consultants interaction with residents and active participation may increase likelihood of achieving clinical competence.